EFEKTIVITAS PEMBERIAN BANTUAN HUKUM OLEH POS BANTUAN HUKUM (POSBAKUM) DALAM PERKARA PIDANA DI PENGADILAN NEGERI MAUMERE - Lili Gratia Sau Sabu; I Putu Edi Rusmana; Ni Nyoman Juwita Arsawati; Dewa Ayu Putri Sukadana (Berajah Journal, 2026)
This study aims to analyze the effectiveness of legal aid provision by the Legal Aid Post (Posbakum) in criminal cases at the Maumere District Court and to identify the obstacles affecting its implementation. This research employs an empirical legal method using statutory, conceptual, and factual approaches, with primary data obtained through interviews and observations, and secondary data derived from legal materials and relevant literature. The findings indicate that the implementation of legal aid by Posbakum has been relatively effective, supported by adequate legal regulations, competent law enforcement officers, and the availability of basic service facilities, thereby ensuring the fulfillment of defendants’ rights, including legal assistance, legal information, and defense. However, its effectiveness is not yet optimal due to several constraints, such as limited human resources and budget, low public legal awareness and understanding, geographical challenges of archipelagic regions, and an underdeveloped legal culture. Therefore, efforts are needed to strengthen institutional capacity, increase resources, and enhance legal awareness through continuous socialization and legal education to improve access to justice for underprivileged communities.